Adolescent Sexual and Reproductive Health Knowledge and Behavior: A Scoping Review of Interventions - Ahi, Gerraint Gillan; Rahman, Md Mizanur; Ramli, Rafazila; Safii, Rasitasam; Minoi, Jacey Lynn; Li, Stephanie Chua Hui; Shminan, Ahmad Sofian; Choi, Lee Jun (Public Health of Indonesia, 2025)
Background: Adolescent sexual and reproductive health (SRH) education requires accurate knowledge, understanding of risks, and supportive access to well-being. Objectives: This review aims to assess how knowledge about sexual and reproductive health (SRH) influences adolescent behaviour, identifying barriers, effective strategies, and communication methods. It evaluates interventions like school-based programs and online resources to empower informed decision-making among adolescents regarding SRH. Method: A systematic search from January 2013 yielded 14 articles, mostly quantitative studies involving adolescents aged 14-19. A narrative analysis identified two main themes: (i) Enhancing SRH knowledge, attitudes, and skills for positive outcomes and innovative intervention strategies. The findings were organized by Endnote 20. Results: The key findings of the review highlight the effectiveness of interventions in improving adolescents’ knowledge, attitudes, and skills related to sexual and reproductive health (SRH). These interventions have shown success in enhancing adolescents’ understanding of SRH issues, fostering positive attitudes toward SRH topics, and building self-efficacy for safe sexual practices. Furthermore, the review highlights the importance of innovative and targeted intervention strategies, such as technology-driven approaches, customized interventions, and the synergistic combination of multiple strategies, to effectively address the diverse needs for SRH of adolescents and promote positive outcomes for SRH. Conclusions: This review emphasizes the impact of SRH interventions on adolescent well-being, advocating for tailored gender-specific approaches, policy integration, and long-term efficacy evaluations for sustained positive outcomes.